Reasons for explantation, demographics, and material analysis of 200 intraocular lens explants. Issue 1 (January 2020) - Neuhann, Tabitha; Yildirim, Timur M.; Son, Hyeck-Soo; Merz, Patrick R.; Khoramnia, Ramin; Auffarth, Gerd U.
Abstract : Purpose: To report demographics, reasons for explantation, and material changes in explanted intraocular lenses (IOLs). Setting: The David J. Apple International Laboratory for Ocular Pathology, Department of Ophthalmology, University of Heidelberg, Germany. Design: Retrospective study laboratory investigation. Methods: IOL explants that were sent consecutively to the laboratory were assessed for demographics (patient sex and age), duration of implant, IOL type, model, power, and reason for IOL explantation. In opacified lenses histological staining, scanning electron microscopy, and energy-dispersive X-ray spectroscopy was performed. Results: The analysis included 200 IOLs that were explanted in median after 5.8 years. The median time the IOL was in the eye was 5.8 years. IOL opacification was the main cause for explantation in 153 (76.5%) cases. Only 27 (13.5%) were explanted due to dislocation. Evaluation of IOL type showed that 167 (83.5%) were made from hydrophilic acrylic material, with 125 (62%) from hydrophilic acrylic material with a hydrophobic surface coating. Analysis of opacities revealed superficial and subsurface deposits of calcium phosphate in most of the opacified lenses (152/153). In total, 22 different manufacturers were represented, with 119 (59.5%) lenses from a single manufacturer. Conclusion: In this cross-sectional study, late IOL calcification was the main reason for IOL explantation. The second most common reason was IOL dislocation. Most explants were lenses from a single manufacturer exchanged due to primary IOL calcification. Abstract : This retrospective cross-sectional study of 200 explanted intraocular lenses (IOLs) reveals the major cause for explantation to be late postoperative IOL calcification.